Ayat-Ayat Damai dalam Al-Qurâ€™an - Wajdi, Firdaus (Jurnal Studi Al-Qur’an, 2009)
This article examines what so called peace verses of the Holy Quran. The verses are searched through the digital Quran, classified, and explained properly to get the appropriate meaning. This study then concludes that there are a lot of verses in the Quran teach peace. This hopefully will make peace as one of the prioritize point in making decision for Islamic society